Analysis of the adaptability of marine hydrate in-situ separator for sand removal to production volume. Issue 4 (4th March 2023) - Qiu, Shunzuo; Wang, Guorong; Zhong, Lin; Fang, Xing
ABSTRACT: The fluctuating production volume puts high demands on the adaptability of the natural gas hydrate in-situ separator. In this paper, based on the structure of the spiral separator and hydrocyclone, the adaptability of the in-situ separator was studied in terms of the influence of production volume on velocity, distribution phase (NGH and sand), separation efficiency, and pressure drop. The results indicate that with the increase of production volume, the velocities increase continuously, and the pressure drop increases sharply, the hydrate phase gathers toward the center and the sand phase gathers toward the wall, the separation efficiency increases and then tends to be stable or decreases. There is a better range of production volume. The better production volume of the spiral separator and the hydrocyclone separator are 60 ~ 80 m 3 /h and 3.5 ~ 6.5 m 3 /h, respectively. The results show that in-situ separators have certain adaptability to production volume. Furthermore, different types of separators have different adaptability. The research results provide some theoretical guidance for the parameters of the desanding process and the selection of in-situ separators for NGH mining.